(untitled) (Revista Sistemas de Producción Agroecológicos, 2015)
In the area of ​​the Colombian high plains it has witnessed a high potential for recovery of degraded areas, carbon capture and storage (C), since there are large tracts of grazing systems therefore could implement projects that lead to reduction emissions of greenhouse gases (GHG), particularly carbon dioxide (CO2), which may be similar to some secondary native forest ecosystems. Dissemination is to contribute to the reflection on the environmental risks that might be incurred to transform a natural grassland ecosystem and the eastern plains of Colombia. Initially a general description of what is carbon sequestration, the carbon cycle, climate change and greenhouse gases, Kyoto protocol, pastoral system with carbon sink parameters determined in carbon sequestration, production takes place Aerial and ground net primary, retention and accumulation of C in soils under pastures of introduced grasses. Identification of the most important agro-ecological and socio-economic conditions of the Colombian high plains, which provide the largest number of items on offer that gives you the subregion to carbon sequestration in poor soils, climate, infrastructure and human resources is also made, performing a comparative analysis between the agroclimatological requirements and carbon capture and production system, where the main opportunities and strengths of the issue are set. It is concluded that the generation of fodder adapted to marginal soils is key to maximizing the benefits of improved pastures, and increase carbon sequestration pastures can be part agroforestry systems, with positive effects on crop yields and mitigation greenhouse effect.